2014
DOI: 10.1186/s13073-014-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ethnic genome-wide association studies: advantages and challenges of mapping in diverse populations

Abstract: Genome-wide association studies (GWASs) are the method most often used by geneticists to interrogate the human genome, and they provide a cost-effective way to identify the genetic variants underpinning complex traits and diseases. Most initial GWASs have focused on genetically homogeneous cohorts from European populations given the limited availability of ethnic minority samples and so as to limit population stratification effects. Transethnic studies have been invaluable in explaining the heritability of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 116 publications
4
165
0
Order By: Relevance
“…9 At the highly complex end of the polygenicity spectrum, we and others have shown that the utility of polygenic risk inferences and the heritable phenotypic variance explained in diverse populations is improved with more diverse cohorts. 92,95 Standard single-ancestry GWASs typically apply linear mixed model approaches and/or incorporate principal components as covariates to control for confounding from population structure with primarily Europeandescent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…9 At the highly complex end of the polygenicity spectrum, we and others have shown that the utility of polygenic risk inferences and the heritable phenotypic variance explained in diverse populations is improved with more diverse cohorts. 92,95 Standard single-ancestry GWASs typically apply linear mixed model approaches and/or incorporate principal components as covariates to control for confounding from population structure with primarily Europeandescent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the LD background, one interesting approach is to identify conserved GWAS associations from distinct ethnicity background, a method known as trans-ethnic analysis. 59 While the method has been proven to improve the overall prediction of causality, such approach may lose certain ethnicity-specific GWAS signals originating from ethnic-specific heterozygosity of the region.…”
Section: In Silico Analysis: Prediction Of Functional Enhancer Variantsmentioning
confidence: 99%
“…Since the lead SNP is unlikely to be the causal variant, this low replication rate is a general problem for trans-ethnic studies. 5 The inability to account for genetic distance between neighboring SNPs and genetic heterogeneity (e.g., locus and allele heterogeneity and variation in LD between populations) are both potential thwarting factors in the endeavor to identify trans-ethnic disease loci.…”
Section: Introductionmentioning
confidence: 99%